Relationship of human papillomavirus infection with adverse outcomes in pregnancy and childbirth: an integrative review (Research, Society and Development, 2022)
The Human Papilloma Virus (HPV) is one of the viruses that most affects the world's population. Its dissemination can lead to negative outcomes, including some types of cancer. However, when present during pregnancy, it seems to be linked to numerous pathological conditions ranging from premature birth to fetal death. Thus, it is imperative to investigate such an occurrence. Our aim was to assess the relationship between HPV infection and adverse outcomes in pregnancy and childbirth. For this, an integrative review on the subject was conducted in the PubMed, CINAHL and Scopus databases. Other findings were identified on the AskMEDLINE platform. After crossing the terms HPV, Pregnancy and Adverse Pregnancy Outcome, 115 studies were identified. Of these, only 10 fit the question proposed and the eligibility criteria outlined. When identified in pregnant women, the main adverse outcomes caused by HPV infection were premature rupture of membranes, premature birth, and spontaneous abortion. New studies need to expand investigations about the subtype of HPV and its complications in pregnancy.